Activation of dopamine D1 receptors does not affect D2 receptor-mediated inhibition of acetylcholine release in rabbit striatum - Dolezal, V; Jackisch, R; Hertting, G; Allgaier, C (Naunyn-Schmiedeberg's archives of pharmacology, 1992)
The possible involvement of dopamine D1 receptors in the regulation of acetylcholine release in the rabbit caudate nucleus was investigated. Caudate slices, preincubated with [3H]choline, were superfused continuously and subjected to electrical field stimulation with only a single pulse. In agreement with the view that the release of acetylcholine evoked by a single electrical pulse is not influenced by endogenous transmitters, atropine and domperidone failed to increase the evoked release of [3H]acetylcholine, whereas oxotremorine and quinpirole caused a concentration-dependent inhibition of transmitter release. Neither the dopamine D1 receptor antagonist SCH 23390 nor the D1 agonist SKF 38393 in a concentration range of 0.01-1 mumol/l changed the evoked [3H]acetylcholine release. The inhibitory effect of the dopamine D2 receptor agonist quinpirole was virtually abolished in the presence of 0.1 mumol/l domperidone and diminished in the presence of 1 mumol/l SCH 23390. It remained unchanged in the presence of 1 mumol/l SKF 38393. It is concluded that the inhibition of acetylcholine release by dopamine is mediated exclusively via presynaptic dopamine D2 receptors and that the antagonistic effect of SCH 23390 on the inhibition of acetylcholine release by quinpirole is due to its interaction with dopamine D2 rather than D1 receptors located on cholinergic nerve terminals.
Keywords: receptory dopaminu D1; Corpus Striatum; dopamin; dopaminové látky; Electrophysiology; Electric Stimulation; acetylcholin; Receptors, Dopamine; Female; elektrofyziologie; zvířata; corpus striatum; Receptors, Dopamine D1; receptory dopaminu D2; receptory dopaminové; Acetylcholine; Dopamine Agents; ženské pohlaví; Male; Dopamine; králíci; Animals; elektrická stimulace; mužské pohlaví; Rabbits; Receptors, Dopamine D2